2011
DOI: 10.1016/j.ab.2010.08.034
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic bead-based protein kinase assay with dual detection techniques

Abstract: A novel magnetic bead-based protein kinase assay was developed using MALDI-TOF mass spectrometry (MALDI-TOF MS) and immuno-chemifluorescence as two independent detection techniques. Abltide substrate was immobilized onto magnetic beads via non-covalent biotin-streptavidin interactions. This non-covalent immobilization strategy facilitated peptide release and allowed MALDI-TOF MS analysis of substrate phosphorylation. The use of magnetic beads provided rapid sample handling and allowed secondary analysis by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In a drugscreening context, magnetic bead assays have been applied in a functional assay of protein kinase activity and in a highthroughput one-bead-one-compound screening system, among other assay systems. 9,10 Importantly, magnetic beads have been used for isolation of target proteins from crude bacterial and mammalian cell lysates, then incorporated in a specific assay system.…”
Section: Introductionmentioning
confidence: 99%
“…In a drugscreening context, magnetic bead assays have been applied in a functional assay of protein kinase activity and in a highthroughput one-bead-one-compound screening system, among other assay systems. 9,10 Importantly, magnetic beads have been used for isolation of target proteins from crude bacterial and mammalian cell lysates, then incorporated in a specific assay system.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that magnetic beads are a powerful tool for hybrid and solid-phase protein kinase assays, offering separation and suitability to automated procedures as well as favorable analysis by MALDI-TOF MS. 2425 To pull out protein kinase products from kinase reaction mixtures by magnetic beads through DNA hybridization for detecting degree of phosphorylation, we investigated the immobilization of the complementary thiol-modified oligonucleotide (5′-HS GTACTTCCTTAAACGACGCAGG-3′) on magnetic beads. First, to prevent nonspecific interactions, a poly(ethylene glycol) (PEG) spacer linker was grafted onto the surface of magnetic beads according as previously reported (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation ratio of Abltide immobilized on magnetic beads was determined according to the previously described computational method (47). …”
Section: Methodsmentioning
confidence: 99%
“…As an alternative strategy to decrease background after phosphorylation, biotin-tagged peptide substrates can be captured onto streptavidin-coated magnetic beads (46) prior to MALDI-TOF analysis. We recently extended this work to create a practical kinase activity screening assay and demonstrated rapid determination of IC 50 for small-molecule kinase inhibitors (47). In this study, we have used Fmoc solid-phase peptide synthesis to install diblock linkers terminated by a photocleavable group onto paramagnetic particles, tethered substrate peptides, and validated these conjugates as reporters of protein kinase activity and inhibition using a MALDI-TOF readout (Figure 1).…”
Section: Introductionmentioning
confidence: 99%